SYARAT ADANYA PERSETUJUAN ISTERI UNTUK BERPOLIGAMI (ANALISIS USHUL FIKIH SYAFI‘ĪYYAH TERHADAP UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974) - Riyandi S (Islam Futura, 2015)
The agreement terms of polygamy in positive law, namely the Marriage Law No. 1 of 1974, Government Regulation No. 9 of 1975, and Compilation of Islamic Law (KHI), is burdensome for men who wish to practice polygamy. Consequently, many men practice polygamy secretly without the approval of the first wife. This study uses qualitative approach. The research result shows that the terms of polygamy in Syafi'īyyah school is capable to bear a living wives and families. The husband is obliged to bear a living either wives or inner birth. According to Syafi'īyyah school no approval requirement for polygamous wives. According to Marriage Law No. 1 of 1974, Government Regulation No. 9 of 1975, and Compilation of Islamic Law (KHI), polygamy should be done without having to seek prior approval to the wife before. If the requisite approvals wife approached with istislahiyah method, it appears that the approval of the wife may be considered as a reason to permit polygamy on the grounds is included in a portion of maqasid syar’iyyah that maintain religion, intellect, lineage, honor and property.